Effect of Blended Learning on Students’ Learning Outcomes: A Meta-Analysis - Lusa, Herman; Adnan, Adnan; Yurniawati, Yurniawati (Jurnal Pendidikan Progresif, 2022)
Effect of Blended Learning on Students’ Learning Outcomes: A Meta-analysis. Objective: This research aims to determine the effect of blended learning implementation in Indonesia between 2016-2020. Methods: This is a meta-analysis study and 27 articles met the criteria analyzed by Revman 5.4. This study reported effect size of blended learning on learning outcomes consisting of subgroups of education levels (elementary school, junior high school, senior high school, vocational education, and college) and subgroups of learning outcomes (knowledge, thinking ability, and attitude). Findings: The theoretical effect size score of Standard Mean Difference or SMD = 1.01 (95% CI [0.802– 1.20). P < 0.00001) for blended learning compared to conventional. Subgroup analysis obtained a high category effect size for Blended Learning’s application according to the level of education and learning achievement. Except for the effect size for attitudes belongs to the moderate category. Conclusion: This study concluded that Blended Learning positively affects knowledge mastery, thinking ability, motivation, and learning independence at all levels of education. Keywords: blended learning, learning outcomes, education level. DOI: 10.23960/jpp.v11.i2.202113